Journal of Management and Governance - Di Pietra, Roberto; Cinquini, Lino.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The Journal of Management and Governance (JMG) is an international journal dedicated to advancing the understanding of corporate governance issues within and throughout privately-held firms, publicly-held corporations and government-controlled organizations. The journal is devoted to exploring the links between management and governance through both theoretical analyses and empirical investigations to improve the understanding of all the rules, codes, principles, practices, processes, mechanisms, structure and relationships, as well as institutions, networks and individuals affecting the way firms and organizations are managed, administered and controlled. Since corporate governance is a multi-faceted subject, the journal aims to analyze a broad spectrum of topics and issues related to the management and governance of firms and organizations: strategies and decision-making; accounting, reporting and information control; measurement issues in governance; relational, cognitive and behavioural based; institutional economics. JMG intends to act as an arena of scientific debate within and among academic and professional networks of researchers with a strong interest in investigating how knowledge, preferences and performance are formed and how they influence governance and management practices and policies. Contributions from all areas of business administration (accounting and control, general and strategic management, organizational theory and behaviour, finance and banking) and manuscripts concerning both the private and the public sectors are welcome to the extent that they contribute to these general issues and to the understanding of governance thus broadly defined. JMG is international in authorship and editorship. It follows the internationally shared norms of blind review and research quality standards, but it distinctively and deliberately adheres to a constructive rather than destructive review process approach. The journal has various paper formats and methods. Any research strategy is recognised, as long as it effectively addresses the issue at hand and rigorously adheres to the methodology adopted, in survey research or simulation, a case study or a statistical analysis. Officially cited as: J Manag Gov.
Keywords: Accounting; Bookkeeping; Management; Industrial organization; Sociology; Management; Accounting/Auditing.; Industrial Organization; Sociology, general